Double-blind study on materials testing with Applied Kinesiology - Staehle, Hans Jörg; Koch, Martin Jean; Pioch, Thomas (Journal of dental research, 2005)
Applied Kinesiology (AK) is a scientifically unproven method used in complementary medicine to recognize the (in)tolerance of dental materials. Test-retest reliability of AK was examined. The working hypothesis was the assumption that the reliability of AK would not exceed random chance. Two dentists qualified in AK examined 112 volunteers to determine individual (in)tolerance toward two dental composite materials. After the first examination, 31 subjects were excluded from further testing. At the end of the open test phase, 34 of 81 participants had been classified as “tolerant”, and seven as “intolerant” to both materials. The remaining 40 individuals showed a combination of either tolerant (to material I)/intolerant (to material II), or the reverse (n = 20 each). Retrieval rate was tested under blind conditions. In 14 cases, the results of the open and blinded tests matched, whereas in 26 cases they did not (95% confidence interval, 21%-52%; p = 0.98). This outcome confirmed our working hypothesis.
Gesehen am 26.02.2021